Kajian Dampak Proses Produksi BBM Di PT X Terhadap Lingkungan Dengan Menggunakan Metode Life Cycle Assessment (LCA) - Fajar Hidayat (Prosiding ESEC, 2023)
The fuel industry is one of the industries with the largest emissions contributors in Indonesia. The resulting emissions are greenhouse gas emissions CO2, CH4, N2O and air pollutant gases SOx, NOx, PM. So a Life Cycle Assessment study is needed to analyze or identify the total environmental impact of processing processes in an industry. In this research, the application used was Simapro 9.1. From the results of the running that has been carried out, the environmental impact value for PT Acidification Potential is 8.66E+00 kg SO2 eq/kl, Eutrophication Potential 7.02E+00 kg PO43-eq/kl, Photochemical oxidant formation potential 1.76E-01 Kg C2H4 eq/kl, Abiotic Depletion Non-Fossils 3.49E-03 kg Sb eq/kl, Abiotic depletion (fossil fuel) of 1.26E+04 MJ/kl, human toxicity of 8.86E+02 kg 1.4-DB eq/kl,. Based on the results obtained by the GWP impact hotspot on the market for electricity process unit, a program is recommended to reduce the use of generators by switching to renewable energy sources, solar cells to produce electricity consumed by the unit. The hotspot for the impact of water use is the process generator unit which is recommended for processing office waste water and changing fuel transportation fuel to environmentally friendly fuel such as Diesel B30.